Corporate governance and financial performance of asset managers in South Africa - Mpai, Abygale (Graduate School of Business (GSB), 2025)
Corporate governance plays an important role in the creation of long-term value and the protection of shareholders and other stakeholders' interests. This research study examines the influence of corporate governance characteristics (board size, board independence, board chairman independence, audit committee independence, and audit committee financial expertise) on the financial performance of asset management firms in South Africa. The proxy for financial performance is Return on Assets. The study employed the fixed and random effects panel regression techniques to estimate a panel data of 11 asset management firms in South Africa from 2012 to 2023. The results of the analysis show a positive and significant relationship between Return on Assets, board chairman independence, and audit committee financial expertise. While the relationship between board independence and Return on Assets is observed to be positive, it is not statistically significant. By contrast, board size and audit committee independence ratio showed no significant relationship with Return on Assets. Therefore, this study recommends the appointment of an independent non-executive chairman on the board of directors to achieve enhanced directorship independence and improved monitoring and supervisory responsibilities within the organisation. Furthermore, South African asset management firms should consider drafting more members with financial expertise into the audit committee and, in particular, directors with a background in accounting, audit, regulation, compliance, internal controls, and enterprise risk management.